Pesticidal activity of leaves and seeds extracts of Tephrosia vogelii Hook. f. and Ricinus communis L. on insects damaging crops and stored food - Nizigiyimana, Liberata; Ngendakuriyo, Alexis; Ngezahayo, Jeremie; Nihorimbere, Manasse; Katihabwa, Aloys; Nduwarugira, Deogratias (European Scientific Journal, ESJ, 2026)
Synthetic pesticides and biopesticides are currently used to control insect pests of crops and harvests. However, biopesticides are more highly recommended because they are environmentally friendly and safe for human health. This study aimed to highlight the pesticidal effect of Tephrosia vogelii and Ricinus communis on four insects: Spodoptera frugiperda, Aphis fabae, Acanthoscelides obtectus, and Sitophilus zeamais. The leaves and seeds of these plants were collected from the fields and analyzed in the laboratory to perform phytochemical screening and test their toxicity to these insects. Results showed that the phytochemistry of the two plants varied from one plant to another and from one extract to another. Aqueous extracts of fresh T. vogelii and R. communis leaves (125 g/L and 250 g/L, respectively) resulted in mortality rates exceeding 50% for A. fabae. Aqueous extracts of T. vogelii leaves were more effective than those of R. communis leaves against S. frugiperda in terms of mortality rates. LD50 of aqueous extracts of T. vogelii leaves was 114 g/L for A. fabae. Most organic extracts (4 mg/L) of both plants achieved mortality rates exceeding 60% for A. obtectus and S. zeamais. Hexane extract (4 mg/L) of T. vogelii leaves and seeds showed better results for treating A. obtectus (LD50 = 1 mg/L–1.33 mg/L). Similarly, hexane extract of T. vogelii seeds showed better results for treating S. zeamais (LD50=1.66 mg/ml). Therefore, it can be concluded that R. communis and T. vogelii could be alternative treatments for insect pests of crops and harvests.